Does TB stigma affect emotion recognition? A study with a Portuguese sample - Nascimento, T.; Bianchi, M. (Psicologia, 2021)
TB stigma constitutes a majo rbarrier to disease control and social distress. This study aims to understand better the inherent social processes on the perception of emotions. Thus far, the specific role of TB stigma in this respect was not tested. We hypothesize that individuals in TB treatment (vs. a control non-clinical group) would identify more negative emotions in the faces of others, specifically rejecting emotions(e.g., disgust) when preoccupied with TB stigma. Twogroups of participants completed a questionnaire with 23 faces, identified the emotions portrayed in the pictures, and reported their level of Stigma Consciousness, Interpersonal-Rejection Related to Stigma, and Rejection Sensitivity. Results show that the two groups significantly differ in their perceptions of negative emotions: participants intreatment identify less disgust and more sadness, fear, and anger versus the control group. Findings are discussed concerning the literature on stigma and its consequences.